Absolute essentials of advertising - Turnbull, Sarah, Dr (Routledge, 2022)
"This concise textbook provides a comprehensive and clear overview of Advertising theory and practice. Each chapter covers the essential aspects of the subject matter, provides a supplement for teaching and acts as a valuable revision guide. Split over three core parts, the book begins with a consideration of the role and function of advertising, the customer journey, advertising theory, planning and strategy, and moves on to the creative development process, media planning and strategy. The final chapter considers the industry as a whole and the reality of practice, outlining roles within agencies to highlight employability opportunities to students. To aid learning, each chapter contains brief real-life examples and includes questions to encourage the reader to consider how practical examples can be applied. Written by a well-renowned textbook author, this short form textbook is suitable for students at all levels studying Advertising. At Undergraduate level, the book provides a valuable support for traditional or blended online teaching. For Postgraduate and MBA students, as well as those studying for professional qualifications, the book also provides a valuable resource"- Resumé vydavatele
Keywords: internetová reklama; reklama a propagace; strategický management; Internet advertising; advertising; strategic planning; elektronické knihy; učebnice vysokých škol; electronic books; textbooks (higher)